2013
DOI: 10.1158/1078-0432.ccr-12-2721
|View full text |Cite
|
Sign up to set email alerts
|

Number of Target Lesions for EASL and Modified RECIST to Predict Survivals in Hepatocellular Carcinoma Treated with Chemoembolization

Abstract: Purposes: To date, most studies about the optimal number of target lesions for enhancement criteria for hepatocellular carcinoma (HCC) have focused on cross-sectional analyses of concordance. We investigated the optimal number of target lesions for European Association for the Study of the Liver (EASL) and modified Response Evaluation Criteria in Solid Tumors (mRECIST) guidelines in predicting overall survival (OS).Experimental Design: We analyzed 254 consecutive treatment-na€ ve patients with HCC having at le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 33 publications
3
37
0
1
Order By: Relevance
“…Second, our study protocol did not include the assessment of multiple target lesions. However, several recent reports did not confirm the benefits of a multi-lesion assessment in the setting of intraarterial therapies [15]. Specifically, semi-automated 3D analysis offers a higher diagnostic accuracy and improved reproducibility of measurements making it less susceptible to reader bias, thus making multiple lesion analysis unnecessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our study protocol did not include the assessment of multiple target lesions. However, several recent reports did not confirm the benefits of a multi-lesion assessment in the setting of intraarterial therapies [15]. Specifically, semi-automated 3D analysis offers a higher diagnostic accuracy and improved reproducibility of measurements making it less susceptible to reader bias, thus making multiple lesion analysis unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…A single targeted lesion per patient was selected for analysis. The analysis of multiple target lesions was omitted as other studies did not confirm the benefit of this methodology [15]. …”
Section: Methodsmentioning
confidence: 99%
“…Up to two target lesions (selected in order of maximum baseline diameter to represent the entire tumor burden) in the liver were assessed using uni-dimensional measurements for mRECIST according to previous investigations regarding the "optimal number of target lesions" for mRECIST in HCC treated TACE [25,26]. For target lesions, tumor response was quantitatively defined as complete response (CR), indicated by complete disappearance of viable lesions, or partial response (PR), defined as ≥30% decrease from baseline.…”
Section: Assessment Of Treatment Responses Using Mrecist Guidelinesmentioning
confidence: 99%
“…The main open question is whether the use of the mRECIST viable tumor concept for target lesion measurements can bring ORR back as a surrogate for survival. Several clinical trials from investigators around the globe have suggested that this is indeed the case in patients receiving tumor-directed therapies (1,(3)(4)(5). In patients treated with TACE, mRE-CIST ORR of 32% to 57% were observed, with significant correlation between response and overall survival (3,5).…”
Section: Riccardo Lencionimentioning
confidence: 95%
“…In this issue of Clinical Cancer Research, Kim and colleagues (1) show that the assessment of tumor response by modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria (2) predicts overall survival in patients with hepatocellular carcinoma (HCC) treated by transcatheter arterial chemoembolization (TACE). The study confirms the results of several recent investigations conducted in the United States, Europe, and Asia (3)(4)(5).…”
Section: Riccardo Lencionimentioning
confidence: 99%